EFEKTIVITAS MEDIA FLASHCARD BERBASIS QUIZLET TERHADAP KEMAMPUAN SPATIAL THINKING PESERTA DIDIK - Netriwati; Angrini, Putri; Junia Lestari, Refi; Mawaddah Herisa, Ulya Nur; Aprilyana, Layla; Ayuni Suri, Indah Resti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT Research on the effectiveness of learning media has been widely conducted; however, the use of Quizlet-based flashcards has not received optimal attention. Field observations indicate that students’ spatial thinking ability at one public junior high school in Metro City still has room for improvement, as reflected in the average pre-research score of 16.87 out of 40 students. The mental rotation indicator even obtained the lowest score. This condition highlights the need for innovative learning media capable of stimulating students’ spatial skills. This study aims to analyze the effectiveness of Quizlet-based flashcard learning media on students’ spatial thinking abilities. The research method employed a quasi-experimental approach with a one-group pretest–posttest design. The research subjects consisted of 35 ninth-grade students at a public junior high school in Metro City. The research instrument was a spatial thinking ability test consisting of six indicators: spatial relations, frame of reference, projective relations, spatial representation, distance conservation, and mental rotation. Data analysis was conducted using a paired sample t-test to determine the significant difference between pretest and posttest results. The findings showed a significance value of p-value < 0.05, indicating a significant difference between the pretest and posttest scores. Therefore, Quizlet-based flashcard learning media is considered effective in improving students’ spatial thinking abilities.